Calcareous microfossils and paleoenvironmental changes across the Cretaceous-Paleogene (K-Pg) boundary at the Cerro Azul Section, Neuquén Basin, Argentina - Guerra, Rodrigo M.; Concheyro, Andrea; Kochhann, Karlos G. D.; Bom, Marlone H. H.; Ceolin, Daiane; Musso, Telma Belén; Savian, Jairo; Fauth, Gerson (Palaeogeography, Palaeoclimatology, Palaeoecology)
We investigate changes in calcareous nannofossil and ostracod communities, which reflect surface and bottom water conditions, respectively, across the Cretaceous-Paleogene transition (K-Pg) at the Cerro Azul Section, Jagüel Formation, Neuquén Basin, Argentina. The K-Pg transition at the Cerro Azul Section is characterized by calcareous nannofossil and ostracod turnovers, from assemblages dominated by Cretaceous forms to assemblages composed by incoming Danian taxa and several survivor species. These assemblage changes were associated with a collapse in carbonate production at the K-Pg boundary, probably related to a drop of surface water productivity, and a subsequent recovery in the early Danian, as suggested by carbonate content, log(Ba/Fe) and log(Ba/Ti) trends. During the Late Maastrichtian, peak relative abundances of Eiffellithus spp., just before the K-Pg transition, were probably related to enhanced surface water productivity. High abundances of Cervisiella operculata suggest decreased surface productivity during the earliest Danian. This surface productivity collapse may have reduced food availability in the benthic habitat, which probably led to the stablishment of Citherudiae-dominated ostracod assemblages. Upward in the section, increased relative abundances of Braarudosphaera bigelowii, are probably related to overall intensified weathering conditions and, consequently, increased continental runoff and fresh water input. Fil: Guerra, Rodrigo M. Universidad de Vale do Rio dos Sinos; Brasil Fil: Concheyro, Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Kochhann, Karlos G. D. Universidad de Vale do Rio dos Sinos; Brasil Fil: Bom, Marlone H. H. Universidad de Vale do Rio dos Sinos; Brasil Fil: Ceolin, Daiane. Universidad de Vale do Rio dos Sinos; Brasil Fil: Musso, Telma Belén. Consejo Nacional de Investigaciones ...